The Wage Distribution in a Model of the Assignment of Skills to Jobs - Teulings, Coen N. (Journal of Political Economy, 1995)
This paper discusses a general equilibrium model of the assignment of heterogeneous workers to heterogeneous jobs. Both jobs and workers are measured along a continuous one-dimensional scale. The composition of labor supply is represented by a distribution function. Workers maximize their earnings. Highly skilled workers have an absolute advantage in all jobs and a comparative advantage in complex jobs. Utility is represented by a constant elasticity of substitution function defined over the output of an infinite number of jobs. Equilibrium is characterized by a mapping of skills on complexities. The model is able simultaneously to explain the remuneration of skill, the allocation of skills to jobs, and variations in labor demand per job type. Estimation results for the Netherlands for 1982 and 1988 offer support for its relevance. Wage differentials are due mainly to skill differentials in the left tail of the distribution and to differences between jobs in the right tail.